FOXP3serum concentration; a likely predictor of CIN and cervical cancer: Secondary analysis from a case control study at a clinic in South western Uganda - Ssedyabane, Frank; Niyonzima, Nixon; Ngonzi, Joseph; Najjuma, Josephine Nambi; Mudondo, Hope; Okeny, Christopher; Nuwashaba, Doreen; Tusubira, Deusdedit (Gynecologic Oncology Reports, 2024)
Biomarkers including Forkhead/ winged-helix transcription factor boxP3 have been proposed in immune-histochemical techniques to diagnose cervical lesions, but can be objectively quantified and measured in blood using methods that can be standardised. In this study we quantified the serum FOXP3 concentrations and assessed their association with cervical lesions at the cervical cancer clinic of Mbarara Regional Hospital (MRRH) South western Uganda. We performed secondary analysis on archived serums amples from a previous unmatched case control study in which we recruited 90 cervical cancer (CC) cases, 90 cervical intraepithelialneoplasia(CIN) cases before any form of treatment and 90 controls. Clinical and demographic data were recorded. We measured FOXP3 concentrations using quantitative ELISA. We performed descriptive statistics and logistic regression in STATA17and took P-values of < 0.05 as statistically significant. The mean concentration of FOXP3 was higher in serum samples from CC cases compared with CIN cases and controls, and this difference was statistically significant (Pvalue<0.001). More than half (52/90,58%) of serum samples from CC cases had FOXP3 concentrations greater than 0.0545ng/ml(Pvalue < 0.001). Increase serum FOXP3 expression was not associated with CIN. Increase in serum FOXP3 concentrations were observed to increase the chances of CC by 2times (OR:2.094, Pvalue0.038,95%CI:1.042–––4.209). Serum FOXP3 is likely associated with cervical lesions especially CC in our study population. Serum FOXP3 testing may be useful in resource limited settings to aid detection of such lesions given the challenges associated with cytology and VIA. We recommend diagnostic utility studies for circulating FOXP3 as a biomarker for detection of cervical cancer.
Keywords: FOXP3; Cervical cancer; Cervical Intraepithelial Neoplasia; Association